The present status of off-pump coronary artery bypass grafting. - Abu-Omar, Y; Taggart, D (2009)
Coronary revascularisation using cardiopulmonary bypass remains the gold standard treatment for coronary artery disease. Over the past decade, techniques of revascularisation on the beating heart without the use of cardiopulmonary bypass (off-pump surgery) have evolved with an attempt to reduce the potential deleterious effects of extracorporeal circulation. Several trials have reported a significant reduction in morbidity with avoidance of cardiopulmonary bypass, while large observational studies have also reported a reduction in mortality. Complete avoidance of aortic manipulation by using off-pump techniques and composite grafts may add an additional benefit particularly in patients at highest risk of stroke. The impact of this mode of revascularisation has probably been underestimated especially in an era where surgical revascularisation is being increasingly undertaken in older patients with significant comorbidities. In this contribution, the current evidence from randomised trials, meta-analyses and observational studies is critically reviewed.